(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2023)
The main problems in this study were the difficulty of students in understanding the learning materials provided by the teacher at school, the lack of parental attention in guiding and accompanying their children’s learning at home, the lack of time for parents to guide and accompany their children to study at home, the lack of attention from other people. old in time management. The type of research used is descriptive qualitative research. This research was conducted at SD Negeri 163/VIII Sungai Jernih, Muara Tabir District, Tebo Regency. The subjects in this study were students in grades 3, 4 and 5 and the parents of these students. This research was conducted in the 2020/2021 academic year. Data collection techniques used are observation, questionnaires, interviews, and documentation. The sample in this study was 30 students in class III, 30 students in IV and 30 in V. The result of this study is that the role of parents in determining student achievement in school is very large. The difficulty of parents in managing their children’s study time, not wanting to know how their children’s learning progress, can cause children not to succeed in their studies. On the other hand, parents who always pay attention to their children, especially attention to their learning activities at home, make children more active and more enthusiastic in learning. So that learning outcomes or learning achievements achieved by students become better.